The acute toxicity study GIZH-290 in mice - S. V. Alekseeva; A. V. Sorokina; A. V. Volkova; V. V. Zabrodina; I. A. Miroshkina; K. S. Kachalov; I. V. Alekseev; A. D. Zaharov (Фармакокинетика и Фармакодинамика, 2021)
Acute toxicity testing is a commonly accepted procedure for preclinical testing of the safety of potential drugs. The compound GIZh-290, which is a derivative of 4-phenylpyrrolidone– 2,6 - dimethylanilide (2-oxo-4-phenylpyrrolidine-1-yl) acetic acid and has a nootropic and anticonvulsant effect, was studied. The results obtained after a single oral and intraperitoneal administration to mice allow us to attribute GIZH-290 to the 4th class of toxicity – "lowtoxic substances". The study revealed the neurotoxic effects of GIZH-290, which may be due to the main pharmacological activity of the compound used in sublethal doses.